(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The contribution reports the paper given by Don Luigi Ciotti during the Summer School on Organized Crime 2019 “Mafias and women” at the University of Milan. The author addresses the issue of women’s detachment from the Mafias and the necessity to listen to their cry for help, through the most significant witnesses he met during his long experience of commitment and fight against the Mafias.